2021
DOI: 10.3847/psj/ac3d86
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence for Wet Accretion of Inner Solar System Planetesimals from Meteorites Chelyabinsk and Benenitra

Abstract: We investigated the hydrogen isotopic compositions and water contents of pyroxenes in two recent ordinary chondrite falls, namely, Chelyabinsk (2013 fall) and Benenitra (2018 fall), and compared them to three ordinary chondrite Antarctic finds, namely, Graves Nunataks GRA 06179, Larkman Nunatak LAR 12241, and Dominion Range DOM 10035. The pyroxene minerals in Benenitra and Chelyabinsk are hydrated (∼0.018–0.087 wt.% H2O) and show D-poor isotopic signatures (δDSMOW from −444‰ to −49‰). On the contrary, the ordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 81 publications
(105 reference statements)
1
11
1
Order By: Relevance
“…The redox state of planetesimals and planetary embryos, usually measured by the FeO concentration in a sample, is crucially affected by the abundance of water, which can raise the overall oxidation state of planetary materials by reaction with other compounds (Elkins-Tanton & Seager 2008a, 2008bLichtenberg et al 2022). The increased oxidation state of magmatic iron meteorites (Bonnand & Halliday 2018;Hilton et al 2022), evidence for degassing from their parent planetesimals (Lichtenberg et al 2021b;Hirschmann et al 2021), fluid flow (Lewis & Jones 2016) and hydrogen incorporation (Piani et al 2020;Jin et al 2021) in ordinary and enstatite chondrites, accretion of water onto achondrites (Sarafian et al 2017) and the devolatilization trend in planetary materials (Wang et al 2019a(Wang et al , 2019b, both in carbonaceous and noncarbonaceous meteorites (Alexander 2019a(Alexander , 2019b, all suggest a substantial initial abundance of highly volatile elements (H, C, N) in inner planetary systems during the disk phase. In addition, uncertainties in high-pressure metal-silicate partitioning allow the earliest accretion phase to be dominated by oxidized materials, fulfilling present-day constraints on Earth's mantle composition by a transition from oxidized to reduced (Siebert et al 2013;Huang et al 2020).…”
Section: Planetesimal Composition and Impact Timingmentioning
confidence: 99%
See 1 more Smart Citation
“…The redox state of planetesimals and planetary embryos, usually measured by the FeO concentration in a sample, is crucially affected by the abundance of water, which can raise the overall oxidation state of planetary materials by reaction with other compounds (Elkins-Tanton & Seager 2008a, 2008bLichtenberg et al 2022). The increased oxidation state of magmatic iron meteorites (Bonnand & Halliday 2018;Hilton et al 2022), evidence for degassing from their parent planetesimals (Lichtenberg et al 2021b;Hirschmann et al 2021), fluid flow (Lewis & Jones 2016) and hydrogen incorporation (Piani et al 2020;Jin et al 2021) in ordinary and enstatite chondrites, accretion of water onto achondrites (Sarafian et al 2017) and the devolatilization trend in planetary materials (Wang et al 2019a(Wang et al , 2019b, both in carbonaceous and noncarbonaceous meteorites (Alexander 2019a(Alexander , 2019b, all suggest a substantial initial abundance of highly volatile elements (H, C, N) in inner planetary systems during the disk phase. In addition, uncertainties in high-pressure metal-silicate partitioning allow the earliest accretion phase to be dominated by oxidized materials, fulfilling present-day constraints on Earth's mantle composition by a transition from oxidized to reduced (Siebert et al 2013;Huang et al 2020).…”
Section: Planetesimal Composition and Impact Timingmentioning
confidence: 99%
“…Only for G dwarfs, such as the Sun, do appreciable quantities of late bombardment hit potentially habitable planets beyond the pre-main-sequence phase. Stephant et al 2021;Jin et al 2021), and somewhat wetter but volatile depleted (0.1 wt%) outside. Carbonaceous asteroids hosting a few wt% of water on average (Alexander et al 2018;Alexander 2019b) motivate our outer compositions.…”
Section: Volatile Delivery Across Physical Scenariosmentioning
confidence: 99%
“…The redox state of planetesimals and planetary embryos, usually measured by the FeO concentration in a sample, is crucially affected by the abundance of water, which can raise the overall oxidation state of planetary materials by reaction with other compounds (Elkins-Tanton & Seager 2008a,b;Lichtenberg et al 2022). The increased oxidation state of magmatic iron meteorites (Bonnand & Halliday 2018;Hilton et al 2022), evidence for degassing from their parent planetesimals (Lichtenberg et al 2021b;Hirschmann et al 2021), fluid flow (Lewis & Jones 2016) and hydrogen incorporation (Piani et al 2020;Jin et al 2021) in ordinary and enstatite chondrites, accretion of water onto achondrites (Sarafian et al 2017) and the devolatilization trend in planetary materials (Wang et al 2019a,b), both in carbonaceous and non-carbonaceous meteorites (Alexander 2019a,b) initial abundance of highly volatile elements (H, C, N) in inner planetary systems during the disk phase. In addition, uncertainties in high-pressure metal-silicate partitioning allow the earliest accretion phase to be dominated by oxidized materials, fulfilling present-day constraints on the Earth's mantle composition by a transition from oxidized to reduced (Siebert et al 2013;Huang et al 2020).…”
Section: Planetesimal Composition and Impact Timingmentioning
confidence: 99%
“…We discuss the physical motivation for each model and the results of the respective bombardment simulations below. of the Solar System after the gas disk phase: relatively dry, volatile-poor (0.001 wt%) bodies inside the asteroid belt (Jin & Bose 2019;Alexander 2019a;Piani et al 2020;Jin et al 2021;Stephant et al 2021), and somewhat wetter but volatile-depleted (0.1 wt%) outside. Carbonaceous asteroids hosting a few wt% of water on average (Alexander et al 2018;Alexander 2019b) motivate our outer compositions.…”
Section: Volatile Delivery Across Physical Scenariosmentioning
confidence: 99%
“…When dusts in the proto-solar disk are irradiated by the solar wind, their compositions will be modi ed, and consequently the composition of planets made from the dusts will also be modi ed by the solar wind. Recently studies on an asteroid (Itokawa; Daly et al 2021) and some meteorite (Jin et al 2021) suggested a role of the solar wind on the water (hydrogen) content in these materials and possible contribution of the solar wind as a source of water on Earth.…”
Section: Introductionmentioning
confidence: 99%